2016
DOI: 10.1021/acs.jpcc.6b06100
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of the (Undoped and Fe-Doped) NiOOH O2 Evolution Electrocatalyst

Abstract: A DFT study was carried out on the atomic and electronic structure of bulk β-NiOOH, with and without substitution of Ni by Fe, examining different stackings and proton distributions in the constituent sheets. The energies of different NiOOH configurations, evaluated at the DFT + U level including dispersion interactions, have very similar values for different stackings and proton distributions, justifying the observed fact that NiOOH is usually obtained in highly disordered form and supporting the assumption t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 56 publications
9
79
0
Order By: Relevance
“…We used the site-specific magnetizations, namely the difference in spin-up and spin-down densities localized on Ni and Fe, as signatures of different oxidation states. Magnetizations have also been used recently to analyze the 3D periodic solid β-NiOOH (19). Whereas other quantitative methods for inferring integer metal oxidation states in the solid state have been developed (38,39), the use of In the reactant and products, nH denotes the stoichiometry of the film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the site-specific magnetizations, namely the difference in spin-up and spin-down densities localized on Ni and Fe, as signatures of different oxidation states. Magnetizations have also been used recently to analyze the 3D periodic solid β-NiOOH (19). Whereas other quantitative methods for inferring integer metal oxidation states in the solid state have been developed (38,39), the use of In the reactant and products, nH denotes the stoichiometry of the film.…”
Section: Resultsmentioning
confidence: 99%
“…The formation or catalytic role of Fe 4+ or other high-valent Fe species was disfavored based on the experimental and computational data. A subsequent operando Mössbauer spectroscopic study, however, showed that significant quantities of Fe 4+ are generated in NiFe-oxyhydroxide catalysts during electrocatalytic water oxidation (18), and the accessibility of Fe 4+ was supported by an independent computational study of such materials (19). These different, and sometimes conflicting, observations highlight the need for an improved understanding of complex materials of this type, ideally drawing upon synergistic contributions from experimental and computational approaches.…”
mentioning
confidence: 99%
“…While precious metals such as Ir and Ru have become standard OER catalysts when working at low pH, alkaline electrolytes allow for the use of abundant, less expensive metals. For example, Ni–M oxyhydroxides such as Ni 1− x Fe x OOH are known to be very active for the OER; however, lack of long-range order and uncontrolled electronic structure stemming from different synthetic methods 2 complicates elucidation of the mechanism(s) by which the OER activity is improved 3–5 . In fact, recent reports question whether Fe is part of the catalytic cycle or if it promotes partial charge transfer between Ni and Fe metal centers 2,4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ni–M oxyhydroxides such as Ni 1− x Fe x OOH are known to be very active for the OER; however, lack of long-range order and uncontrolled electronic structure stemming from different synthetic methods 2 complicates elucidation of the mechanism(s) by which the OER activity is improved 3–5 . In fact, recent reports question whether Fe is part of the catalytic cycle or if it promotes partial charge transfer between Ni and Fe metal centers 2,4,6 . Additionally, recent work on Ni–Fe oxyhydroxides demonstrated that a significant portion of the measured OER current may be due to other processes and highlighted the need for careful electrochemical analysis of what reactions are contributing to the high activities reported 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation